Gestão escolar na pandemia: demandas, formação e orientação - Noelma Nascimento Pinheiro (2023)
On January 30, 2020, the World Health Organization (WHO) declared a Public Health Emergency of International Concern over COVID-19. Faced with a pandemic scenario, isolat ion and social distancing were preventive measures adopted in the world, aimed at reducing and controlling the number of deaths that grew alarmingly (In Brazil alone there were more than 600,000 deaths by 2022.). As of March 17, 2020, Brazilian school institutions suspended face-to-face classes and then joined Emergency Remote Teaching as a way of continuing the teaching-learning process. The present investigative work has as main objective to raise and analyze the continuing education proposals offered to school managers in the period of the Covid-19 pandemic, as well as the main challenges faced by two schools in Ipatinga-MG that offer Early Childhood Education and Elementary School Early Years. Based on exploratory, documental and bibliographical research, the qualitative study with data treated through Bardin's Content Analysis will involve the use of secondary data from other research already published on the subject and from semi-structured interviews. In this perspective, the contribution of authors such as Brejon (1967), Mascaro (1968), Paro (2010), Ribeiro (1968), Sander (2009) and Teixeira (1968) are sources of productions that corroborate the theoretical foundation in question and make necessary in conducting the proposed research. Brejon (1967), Mascaro (1968), Ribeiro (1968) and Teixeira (1968) present a historical point of view of Brazilian school administration; which already allows us to ratify that the scarce continuing education for school managers is not a new problem. Paro (2010) and Sander (2009) discuss the topic today, with new denominations incorporated into the term administration and the concern with rebuilding the technical and political profile of the educational manager. Based on the Literature Review and data analysis, we concluded that some education networks did not offer the continuing education necessary for school administrators. In other cases, training was insufficient to meet demands; however, it is possible to state that, even in the face of so many difficulties, education professionals, managers and teachers, have shown an admirable capacity for resilience and adaptability in facing Covid-19. Therefore, it is intended that, in the end, this work can contribute to the improvement of teaching, in order to produce a podcast for the “Entre Docentes” platform, from Gestrado, with the theme of continuing education for managers in the pandemic.